2016
DOI: 10.1039/c5sc04652a
|View full text |Cite
|
Sign up to set email alerts
|

[NiIII(OMe)]-mediated reductive activation of CO2 affording a Ni(κ1-OCO) complex

Abstract: We report a novel pathway for the reductive activation of CO2 by the [NiIII(OMe)(P(C6H3-3-SiMe3-2-S)3)]– complex, yielding the [NiIII(κ1-OCO˙–)(P(C6H3-3-SiMe3-2-S)3)]– complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… Since then, several similar Ni­(η 2 -CO 2 ) complexes have been reported, , including a unique five-coordinated Ni­(η 2 -CO 2 ) complex . A unique coordination mode of μ-η 2 ,η 2 -CO 2 in a dinuclear Ni complex was reported by Sadighi and co-workers, and a rare case of Ni III (η 1 -(CO 2 ) • -κ O ) was reported by Chiou, Liaw, and co-workers . Recently a rare case of Ni II (η 1 -CO 2 -κ C ) was reported by Lee (Scheme ).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“… Since then, several similar Ni­(η 2 -CO 2 ) complexes have been reported, , including a unique five-coordinated Ni­(η 2 -CO 2 ) complex . A unique coordination mode of μ-η 2 ,η 2 -CO 2 in a dinuclear Ni complex was reported by Sadighi and co-workers, and a rare case of Ni III (η 1 -(CO 2 ) • -κ O ) was reported by Chiou, Liaw, and co-workers . Recently a rare case of Ni II (η 1 -CO 2 -κ C ) was reported by Lee (Scheme ).…”
mentioning
confidence: 85%
“…60 A unique coordination mode of μ-η 2 ,η 2 -CO 2 in a dinuclear Ni complex was reported by Sadighi and co-workers, 61 and a rare case of Ni III (η 1 -(CO 2 ) • -κ O ) was reported by Chiou, Liaw, and co-workers. 62 Recently a rare case of Ni II (η 1 -CO 2 -κ C ) was reported by Lee 63 (Scheme 2).…”
mentioning
confidence: 99%
“…Treatment of transition-metal–thiolate complexes with O 2 frequently causes ligand-centered oxidation, resulting in the formation of metal–sulfenate, −sulfinate, or −sulfonate species. On the other hand, coordination of chelating ligands containing strongly donating thiolato sulfur(s) is found to help metal-based O 2 activation by lowering the metal redox potential. ,,, Thiolates with noninnocent character also serve as good chelators to help stabilize high-valent complexes. One example of this class is the tetradentate-deprotonated TMS PS3H 3 ligand which contains three thiolates and phosphine. In previous studies, we have demonstrated that treatment of a thiolate-ligated Mn­(I) complex containing a pendant thiol group with O 2 can generate a monomeric O 2 -side-on-bound [PPN]­[Mn IV ( TMS PS3)­(O 2 )] which is metastable in organic solvent and stable in the solid state at ambient temperature (Scheme ). The activation of O 2 is proposed to go through a four-coordinated [Mn II ( TMS PS3)] − intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Having found the {(depe) 2 Fe 0 } fragment capable of reductive C–C bond coupling with CO 2 and C 2 H 4 , its competency in oxalate formation was investigated. Complex 1 was initially targeted because in addition to the design criteria given above, this complex is among only a limited number of isolable transition metal CO 2 complexes, and this stable precoordination may improve the selectivity of reduction. , Furthermore, the bending of the CO 2 bond angle upon coordination could lower the potential required for 1-electron reduction ( E 0 = −1.90 V vs NHE) by alleviating the degree of reorganization required in the transition structure . To date, iron-mediated oxalate formation reactions have been exclusively seen at iron­(I) complexes.…”
Section: Resultsmentioning
confidence: 99%